METAGENOMIC EXPLORATION OF ECO-ENZYME PRODUCTION: UNVEILING ENZYMATIC ACTIVITIES AND MICROBIOTA ABUNDANCE FOR SUSTAINABLE ORGANIC WASTE MANAGEMENT - Prakoso, Haryo Tejo; Permatasari, Galuh Wening; Dimawarnita, Firda; Kalbuadi, Donny (BRIN - Badan Riset dan Inovasi Nasional, 2025)
Globally, organic waste is steadily increasing, raising serious environmental challenges. A promising solution is the conversion of organic waste into Eco-Enzyme (EE), a fermented product widely applied in wastewater treatment, soil improvement, and fertilization. Despite its potential, few studies have characterized EE from a metagenomic perspective. This study examined enzymatic activities and microbial communities during EE production. EE was prepared from pineapple and orange peels mixed with palm sugar and water, then fermented for 90 days. The mixture was analyzed for enzymatic activities including amylase, cellulase, protease, chitinase, lignin and Mn peroxidase, peroxidase, glucanase, and catalase, and linked to waste degradation potential. Metagenomic sequencing using Oxford Nanopore Technology revealed Terrabacteria (83%), dominated by Lacticaseibacillus and Lentilactobacillus, and Proteobacteria (17%) with Acetobacter fabarum prevalent in EE sample. The highest activity was catalase (5107 mU/ml), followed by chitinase, protease, and amylase. These results highlight EE’s microbial and enzymatic complexity, reinforcing its role in sustainable organic waste management.